2019
DOI: 10.1088/1361-6471/ab3f7c
|View full text |Cite
|
Sign up to set email alerts
|

Physics potential of an experiment using LHC neutrinos

Abstract: Neutrinos are abundantly produced in the LHC. Flavour composition and energy reach of the neutrino flux from proton–proton collisions depend on the pseudorapidity η. At large η, energies can exceed the TeV, with a sizeable contribution of the τ flavour. A dedicated detector could intercept this intense neutrino flux in the forward direction, and measure the interaction cross section on nucleons in the unexplored energy range from a few hundred GeV to a few TeV. The high energies of neutrinos result in a larger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…More detailed studies on the detector design and physics sensitivities are reported here for the first time. A recent study of Beni et al [37] has analyzed various locations around the LHC for neutrino detection and has found that, incorporating the background results from FASER, TI12 and TI18 are the best locations among those they considered.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed studies on the detector design and physics sensitivities are reported here for the first time. A recent study of Beni et al [37] has analyzed various locations around the LHC for neutrino detection and has found that, incorporating the background results from FASER, TI12 and TI18 are the best locations among those they considered.…”
Section: Introductionmentioning
confidence: 99%
“…[10], the contributions from W and Z production and decay to neutrinos are studied. They show that neutrinos from weak gauge boson decays populate mostly in the pseudorapidity range of |η| < 4.5, but are negligible in the region η > 6.5 [10]. Figure 9.…”
Section: Muon Neutrinosmentioning
confidence: 99%
“…The Faser collaboration uses a pseudorapidity cut η > 6.87 on particle momenta (here, neutrinos) in its second phase to determine if they enter a detector of radius 1.0 m. Other evaluations for this baseline use η > 6.7 [9]. For a half-cylinder, 2-meter long lead detector covering pseudorapidities η > 6.7, Beni et al [10] used Pythia 8 [16,18] to find ∼ 8, 700 tau neutrino events for a 3, 000 fb −1 integrated luminosity at the LHC. We adopt a minimum pseudorapidity η > 6.87 in this work for definiteness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, attention has turned to opportunities of measuring the interactions of highly energetic tau neutrinos produced by pp collisions at the LHC [5][6][7][8][9][10][11]. Tau neutrino beams would allow for direct tests of lepton universality and to explore tau neutrino PMNS mixing in the traditional three-neutrino mixing paradigm and in scenarios including additional exotic neutrinos.…”
Section: Introductionmentioning
confidence: 99%